2007
DOI: 10.1590/s0034-72992007000300014
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da timpanoplastia no zumbido de pacientes com hipoacusia condutiva: seguimento de seis meses

Abstract: Tympanopl asty is done to eradicate ear pathology and to restore the conductive hearing mechanism (eardrum and ossicles). Some patients, however, do not tolerate tinnitus and question physicians about the results of surgery when tinnitus persists. Aim: to evaluate the progression of tinnitus in patients with conductive hearing loss after tympanoplasty. Study Design: a prospective cohort study. Material and Methods: 23 consecutive patients with tinnitus due to chronic otitis media underwent tympanoplasty. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…McGrew et al (2004) 14 showed that 76 patients (36%) closed the gap by up to 10 dB HL, and 74 patients (34%) attained a final gap around 11 to 20 dB HL. Lima et al (2007) 15 Based on these results, we concluded that there was a statistically significant improvement in the quality of hearing of patients undergoing tympanoplasty (p=0.002). We believe this improvement was due to graft integration and better conditions in the middle ear and ossicular chain as a result of surgery.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…McGrew et al (2004) 14 showed that 76 patients (36%) closed the gap by up to 10 dB HL, and 74 patients (34%) attained a final gap around 11 to 20 dB HL. Lima et al (2007) 15 Based on these results, we concluded that there was a statistically significant improvement in the quality of hearing of patients undergoing tympanoplasty (p=0.002). We believe this improvement was due to graft integration and better conditions in the middle ear and ossicular chain as a result of surgery.…”
Section: Discussionmentioning
confidence: 84%
“…McGrew et al (2004) 14 showed that 76 patients (36%) closed the gap by up to 10 dB HL, and 74 patients (34%) attained a final gap around 11 to 20 dB HL. Lima et al (2007) 15 attained values of 61% and 22%. We attained gap closures of up to 10 dB in 22 patients (56%) and a final gap from 11 to 20 dB HL in 10 patients (26%), results that were better than those of McGrew et al and similar to those of Lima et al This difference with McGrew et al's study may have been because it was a retrospective study.…”
Section: Discussionmentioning
confidence: 92%
“…Albuquerque et al (2009) reported that the tympanic bulla of the rat is very delicate and that bone fractures occur during manipulation of the structure for its opening. This characteristic of the paca is a highly positive point in surgeries of the middle ear since it facilitates access to and manipulation of structures in operations involving the tympanic membrane such as tympanoplasty for the treatment of conductive hearing loss and tinnitus (Lima et al 2007), and the ossicular chain (Ribeiro et al 2005).…”
Section: Discussionmentioning
confidence: 99%